2019
DOI: 10.21873/invivo.11601
|View full text |Cite
|
Sign up to set email alerts
|

Does Aberrant Right Hepatic Artery Influence the Surgical Short- and Long-term Outcome of Pancreatoduodenectomy?

Abstract: Background: Variations in vascular anatomy in pancreaticoduodenectomy for adenocarcinoma of the pancreatic head, aberrant right hepatic artery (αRHA) being the most frequent, may influence oncological outcome, surgical complexity, intra-and postoperative complications, and overall 5-year disease-free and survival rates. Materials and Methods: Between January 1988 and January 2018, 297 consecutive patients underwent pancreaticoduodenectomy at our Institutions and were divided into two groups: Group 1 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 30 publications
1
19
2
Order By: Relevance
“…Regarding long term survival, the studies by Eshuis et al, Crocetti et al, and Kim et al already proved that survival was not affected by aRHA (16,18,26). Our results support these data and reveal the longest median survival of 29 months among all studies included in the systematic review (Figure 4).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Regarding long term survival, the studies by Eshuis et al, Crocetti et al, and Kim et al already proved that survival was not affected by aRHA (16,18,26). Our results support these data and reveal the longest median survival of 29 months among all studies included in the systematic review (Figure 4).…”
Section: Discussionsupporting
confidence: 89%
“…For example, Asano et al had to resect aRHA in 18% of the patients with this anomaly and reported a prolongation of surgery of about 33 minutes (23). Crocetti et al reconstructed 25% of aRHA, which prolonged operating time with 34 minutes (26). Rammohan et al ligated aRHA in 19% and reconstructed it in additional 2% resulting in a 60 minutes difference in the operating time (19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Others also reported that the frequency of aberrant RHA was 13.8%-20.7% after Hiatt's classification, and these results were similar to those reported by Hiatt. 12,18,[34][35][36][37][38][39][40][41] Although aberrant RHA classified by Hiatt's types originate from SMA, there are other rare variations of aberrant RHA that originate from the aorta, left gastric artery, celiac artery, and gastroduodenal artery. 39 The main origin of aberrant RHA was SMA, celiac artery, and aorta, and the frequency was reported to be 74.1%-80.7%, 18.0%-19.2%, and 7.9%, respectively.…”
Section: Variation Of Hepatic Arterymentioning
confidence: 99%